2019
DOI: 10.1177/0379572119892405
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Dietary Diversity Among Women of Reproductive Age and Agricultural Diversity in Rural Tanzania

Abstract: Background: Agriculture can influence diets through consumption of home-produced foods or increased purchasing power derived from sale of agricultural commodities. Objective: This article explores cross-sectional relationships between agricultural diversification and dietary diversity (a proxy for micronutrient adequacy) among women of reproductive age in rural Tanzania. Methods: Dietary diversity was measured using the women’s minimum dietary diversity score indicator. Data were analyzed from the baseline sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 18 publications
6
20
1
Order By: Relevance
“…Our results showed to be better than the 25% of WRA reaching a diverse diet in Gitagia, Kenya (2019) [30], and Chakona, South Africa (2017) [29]. In the study of Bellows and colleagues (2019), only 10% of women of reproductive age in rural Tanzania consume at least five food groups [28], far below what was seen in our findings. Also, in our study, women with low SES had significantly lower DDS than those in the medium and high SES (p < 0.05).…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Our results showed to be better than the 25% of WRA reaching a diverse diet in Gitagia, Kenya (2019) [30], and Chakona, South Africa (2017) [29]. In the study of Bellows and colleagues (2019), only 10% of women of reproductive age in rural Tanzania consume at least five food groups [28], far below what was seen in our findings. Also, in our study, women with low SES had significantly lower DDS than those in the medium and high SES (p < 0.05).…”
Section: Discussioncontrasting
confidence: 80%
“…DDS showed an average score lower than the 5-point cut-off proposed by FAO [11]. When analyzed by country, only Peru and Ecuador reached the MDD-W. Several studies conducted in African populations using the same methodology have obtained worse results [7,[28][29][30]. According to the MDD-W threshold of five or more food groups, 57.7% of WRA living in Latin America have a diverse diet.…”
Section: Discussionmentioning
confidence: 94%
“…Previous cross-sectional results from our study showed an association between crop diversity, production of pulses and production of vegetables with women's dietary diversity score (Bellows et al, 2019).…”
Section: Discussionsupporting
confidence: 51%
“…community based, food and nutrient intake, food security, low income, maternal nutrition, micronutrients, nutrition-sensitive agriculture, homestead food production, community health workers, dietary diversity, leafy greens (Bellows et al, 2019;Huang et al, 2018;Lander et al, 2019). Micronutrient-dense foods such as vegetables and animal products are often more expensive and perishable than staple grains and therefore less affordable, especially for low-income households (Masters et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation